Inclusive or exclusive? : a missiological analysis of congregations in the Reformed Church in Africa - Sukdaven, Maniraj (University of the Free State, 2006)
With the dismantling of apartheid and all its repressive laws, especially the “Group Areas Act”, people could now choose where they wanted to live. The result was a migration of people from the rural areas to the urban areas where they could be closer to their places of employment, better schools for their children, better infrastructure and amenities. Most of these people did not have the finances to buy land and build houses so they began to settle on available lands surrounding a suburb. On these lands they began building “houses” made of wood and zinc which they called home. These settlements became known as informal settlements or more commonly known as “squatter camps”. This empirical study is focussed on the congregations of the Reformed Church in Africa of one of its regions which together constitutes the RCA Presbytery of Gauteng. These congregations have a predominantly “Indian” membership due to the location of the church buildings which were built during the apartheid era and subjected to the Group Areas Act. The result of this was that these congregations engaged in mission work amongst its own population group. The main intention of the study is to establish how these congregations view these informal settlements that have now come to settle within their congregation boundaries. An attempt is made to answer the question as whether these congregations view the informal settlement as “inclusive” or “exclusive” of their mission work. The terms “inclusivism” and “exclusivism” is not defined as it is understood in the “Theology of Missions”. In the context of this dissertation these terms refers to mission work engaged in by the congregations of the Gauteng Presbytery as to whether it includes or excludes the informal settlements that are to be found in their areas. These terms are also defined vis-à-vis universalism as distinct from universal salvation. A comprehensive study, yet not an exhaustive one, is attempted in order to understand the terms “inclusiveness” and “exclusiveness” in the Old and New Testaments. These terms were also subjected to an understanding of missions as centripetal and centrifugal. The relationship between church and mission is investigated so as to determine whether these are two separate identities or whether there is an inseparable link between the two. The research is structured so that the sample of the universe being researched would provide data that is representative of the RCA Presbytery of Gauteng. The questionnaire instrument of measurement was adopted to gather information for this research. The sampling method employed was the probability, stratified simple random sampling method. Attention is given to the era in which the Reformed Church in Africa was born as well as its ethos, which is encapsulated predominantly in the Laudium Declaration. Due to the emphasis of the Laudium Declaration on evangelism, a short critical comparison is made between the Laudium Declaration and its relationship to the praxis of missions as understood by the congregations within the RCA Presbytery of Gauteng. Chapter seven is the analysis of the information generated from the questionnaires. The concluding chapter offers information, suggestions and makes recommendations to the RCA Presbytery of Gauteng on how it is presently engaged in missions in relation to the informal settlements, which changes are advisable and how it should understand the relationship between church and missions. The ultimate purpose of this research is to understand whether the RCA congregations in the Presbytery of Gauteng has experienced a shift in its mission obligation from missions only to the Indian culture during the apartheid era to include other cultural groups.

Met die einde van apartheid en al sy beperkende wetgewing, veral die Groepgebiedewetgewing, kon mense nou kies waar hulle wil lewe. Die gevolg was n verskuiwing van mense van die plattelandse gebiede na die stedelike gebiede waar hulle nader aan werksgeleenthede, beter skole vir hulle kinders, beter infrastruktuur en geriewe kon wees. Die meeste van hierdie mense het nie die geldelike vermoe gehad om grond te koop en huise te bou. Daarom het hulle op beskikbare grond rondom n voorstad geplak. Op hierdie grond het hulle begin blyplek maak uit hout en sinkplate waarna hulle verwys het as hulle huis. Hierdie nedersetting het bekend geword as informele nedersettings en meer algemeen as plakkerkampe. Hierdie empiriese studie fokus op die gemeentes van die Reformed Church in een van sy gebiede wat saam die RCA Presbytery of Gauteng vorm. Hierdie gemeentes het oorheersende Indieer lidmaatskap toe te skryf aan die plasing van die kerkgebou wat gedurende die apartheids era opgerig was onderworpe aan bepalings van die Groepgebiede-wetgewing. Die gevolg was dat heirdie gemeentes betrokke was in sending werk onder hulle eie bevolkingsgroep. Die hoofdoel van die studie is om vas te stel hoe hierdie gemeentes die informele nedersettings wat binne hulle gemeente grense ontstaan het, beskou het. nPoging is aangewend om n antwoord te kry oor die vraag of hierdie gemeentes die informele nedersetting ingesluit of uitgesluit het in hulle sendingwerk. Die terme “inklusivisme” en “eksklusivisme” word nie gedefineer soos dit in die “Sending-teologie” verstaan word. In die konteks van hierdie verhandeling verwys hierdie terme na sending werk waarby die gemeentes in die Gauteng Presbytery betrokke is of dit onderskeidelik die informele nedersetting in hulle gebiede in-of-uit sluit. Hierdie terme word aldus gedefinieer teenoor universalisme in onderskeiding van universele verlossing. n omvattende studie, maar nog nie volledig nie, is onderneem in n poging om die terme “inklusiviteit” and “eksklusiviteit” in die Ou en Nuwe Testament te verstaan. Hierdie terme word al dus onderwerp om n verstaan van sending as middepuntsoekend en middepuntvliedend. Die verbonding tussen kerk en sending word ondersoek om so vas te stel of hierdie twee afsonderlike identiteite is of daar n onskeibare skakel tussen hulle twee is. Die navorsing is so gestruktureer so dat die steekproef data verskaf van wat verteenwoordigend is van die RCA Presbytery of Gauteng. Die vraelys, as meetintrument is gebruik om inligting te kry vir die navorsing. Die steekproefmetode is die van waarskynlikheid, met n verdere opsie van stratifikasie. Aandag is gegee aan die tydperk waarbinne die Reformed Church in Africa ontstaan het so wel as sy etos wat oorheersend saam gevat word in die Laudium Declaration. Toe te skryf aan die klem op evangelisasie van die Laudium Declaration, is n kort kritiese vergelyking gemaak tussen die Laudium Declaration en die sendingpraktyk se verstaan by die gemeentes van die RCA Presbytery van Gauteng. Hoofstuk sewe is die analise van inligting gekry uit die vraelys. Die slot hoofstuk bied inligting voorstelle en aanbevelings aan die RCA Presbytery of Gauteng oor hoe dit tans betrokke is in sendingwerk met betrekking tot informele nedersetting wat veranderinge wenslik is en hoe dit die verhouding tussen kerk en sending behoort te verstaan. Die uiteindelike doel van hierdie navorsing is om te verstaan of die RCA gemeentes in die Presbytery of Gauteng n skuif gemaak het in sy sending verpligting van sending slegs vir die Indier kultuur-groep soos ervaar gedurende die apartheid tydperk om ander kultuur-groepe in te sluit.
Dissertation (M.A. (Missiology))--University of the Free State, 2006
Keywords: Centripetal; Church; Exclusivism; Inclusivism; Missio Dei; Centrifugal; Mission of the church; Christianity and other religions